Good Corporate Governance Dalam Perspektif Teori Keagenan - Dwi Urip Wardoyo; Rafiansyah Rahmadani; Putut Tri Hanggoro (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2021)
In running a business, companies are required to have good governance or commonly referred to as good corporate governance. Good corporate governance is a set of rules, practices, and control processes of a company to maximize the value creation of the company as an economic entity based on the application of general basic principles. This article will discuss the concept of good corporate governance with agency theory. Agency theory is the most appropriate basis for understanding corporate governance. Agency theory is a theory that explains the relationship that occurs between the management of the company as an agent and the owner of the company as the principal. Agency relationship is a contract in which one or more people (principals) instruct another person (agent) to perform a service on behalf of the principal and authorize the agent to make the best decisions for the principal.